Micromechanical Thermal Assays of Ca2+-Regulated Thin-Filament Function and Modulation by Hypertrophic Cardiomyopathy Mutants of Human Cardiac Troponin. (14th February 2012) - Brunet, Nicolas M.; Mihajlović, Goran; Aledealat, Khaled; Wang, Fang; Xiong, Peng; von Molnár, Stephan; Chase, P. Bryant
Abstract : Microfabricated thermoelectric controllers can be employed to investigate mechanisms underlying myosin-driven sliding of Ca 2+ -regulated actin and disease-associated mutations in myofilament proteins. Specifically, we examined actin filament sliding—with or without human cardiac troponin (Tn) and α -tropomyosin (Tm)—propelled by rabbit skeletal heavy meromyosin, when temperature was varied continuously over a wide range ( 20–63C ° ). At the upper end of this temperature range, reversible dysregulation of thin filaments occurred at pCa 9 and 5; actomyosin function was unaffected. Tn-Tm enhanced sliding speed at pCa 5 and increased a transition temperature (T t ) between a high activation energy (E a ) but low temperature regime and a lowE a but high temperature regime. This was modulated by factors that alter cross-bridge number and kinetics. Three familial hypertrophic cardiomyopathy (FHC) mutations, cTnI R145G, cTnI K206Q, and cTnT R278C, cause dysregulation at temperatures 5–8C ° lower; the latter two increased speed at pCa 5 at all temperatures.